Compilação de semântica denotacional modular - Tays Cristina do Amaral Pales Soares (2007)
Programming language semantics and syntax can be defined without ambiguities using formal definitions. Denotational Semantics is an approach which allows formal description of language semantics. However, uses of Denotational Semantics face scalability issues. Formal specification of large scale languagesis inherently complex, requiring a model capable of decomposing semantics descriptions in such a way that it is possible to manage its complexity. Multidimensional Semantics proposes a new methodology for development of modular denotational semantic definitions. The functional, domain specific, languageNotus implements the model proposed by this new approach. This work presents a compiler implementation for Notus, which is a language that allows writing syntactic, lexical and semantic definitions incrementally. The modularity is based on the desired language's abstract syntax. A moduleis made for each semantically relevant syntactic construct. This improves the reusability and extensibility in denotational semantics specifications. The Notus compiler produces interpreters for specified languages. Compilation of modular specification poses issues that are also solved in the Notus compiler.